The Effect of Flash Sale and Delivery Experience on Repurchase Decision Mediated by Customer Satisfaction: A SEM-PLS Study on Gen Z Shopee Consumers of Skintific - Misbakhuddin, Agam; Riyoko, Sisno; Widiastuti, Anna (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of flash sales and delivery experience on repurchase decisions with customer satisfaction among Generation Z consumers of Skintific skincare products on Shopee. The population of this study consists of all consumers of Skintific skincare products on Shopee, whose total number is not precisely known. The sample comprised 100 respondents selected using a purposive sampling technique. Instrument testing in this study employed validity and reliability tests. The data analysis method used structural equation modeling (SEM) with SmartPLS software version 3.29. The results indicate that flash sales have no effect on repurchase decisions, delivery experience has a positive and significant effect on repurchase decisions, flash sales have no effect on customer satisfaction, delivery experience has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on repurchase decisions of Skintific skincare products on Shopee among Generation Z consumers. The implication of this study is that Generation Z consumers tend to make repeat purchases because they feel satisfied with the shopping experience they receive, particularly related to service quality and product delivery.